2018
DOI: 10.1371/journal.pone.0189766
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity characterized by pretreatment PET in non-small cell lung cancer patients predicts progression-free survival on EGFR tyrosine kinase inhibitor

Abstract: Intratumoral heterogeneity has been suggested to be an important resistance mechanism leading to treatment failure. We hypothesized that radiologic images could be an alternative method for identification of tumor heterogeneity. We tested heterogeneity textural parameters on pretreatment FDG-PET/CT in order to assess the predictive value of target therapy. Recurred or metastatic non-small cell lung cancer (NSCLC) subjects with an activating EGFR mutation treated with either gefitinib or erlotinib were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Squamous cell carcinoma generally occurs in male and smoking patients. However the driver genes involved remain unclear [3][4][5][6]. Efficacious targeted therapy was achieved in lung adenocarcinoma via the specific targeting of driver genes, such as EGFR and ALK.…”
Section: Introductionmentioning
confidence: 99%
“…Squamous cell carcinoma generally occurs in male and smoking patients. However the driver genes involved remain unclear [3][4][5][6]. Efficacious targeted therapy was achieved in lung adenocarcinoma via the specific targeting of driver genes, such as EGFR and ALK.…”
Section: Introductionmentioning
confidence: 99%
“…With EGFR, findings are conflicting, with some studies predominantly showing high FDG uptake in EGFRmutated tumours, reflecting increased glycolysis through AKT signalling [47], and others showing lower uptake [48]. As well as standard features, such as SUVmax, heterogeneity parameters also show associations with EGFR mutation status [49,50] and value in predicting response and survival following treatment with TKIs [51,52]. Less specific associations between FDG PET radiomics and genetic heterogeneity, but not tumour mutational burden, have been shown in SCLC but not in NSCLC [53].…”
Section: Nsclc: Defining Molecular Mechanisms From Imagingmentioning
confidence: 99%
“…Both genotypic and phenotypic heterogeneity are associated with chemoresistance that have a profound impact on the clinical outcome of lung cancer patients. For instance, at the clinical level, it has been recently suggested that increased metabolic heterogeneity should be considered as a high-risk subpopulation for early EGFR TKI failure [4].…”
Section: Intratumoral Heterogeneitymentioning
confidence: 99%